Il "Cantico Di Frate Sole" Di S. Francesco D'Assisi In S. Massimiliano Maria Kolbe: Testimonianze e interpretazioni nelle "Fonti Kolbiane" - Kumka, Emil (Miscellanea francescana, 2025)
In the Writings of St. Maximilian Kolbe, there are no systematic or comprehensive texts directly addressing the theme of nature. However, the collection of passages selected from his legacy and analysed here, following the verses of the Canticle of the Creatures by St. Francis of Assisi, reveal his understanding and connection with creation. Despite the seven centuries separating the lives of the two saints, some emphases are obviously different, but not, so much so, that numerous similarities and shared perceptions cannot be observed. St. Francis' vision is visible in the stories and experiences of St. Maximilian, not only on an experimental level, but also on a theological and mystical level. With a Marian imprint, fundamental to understanding all Kolbian spirituality, creation finds its incomparable summit in the person of the Immaculate Conception, who, according to the holy martyr, protected and guided creation, and through her, creation was united in praise of God.